Role of posterior auricular muscle to prevent protruding ear after retroauricular ear surgery. Issue 1 (February 2020) - Lee, Jong Cheol; Cheon, Tae-Uk; Lee, Jung On; Shin, Dan Bi; Kwon, Joong Keun
Abstract: Objective: The posterior auricular muscle (PAM) functions in ear projection in normal position and is severed during the retroauricular approach, and some patients complain of a protruding ear postoperatively. This study was designed to determine whether suturing of the severed PAM reduces pinna projection after the retroauricular approach. Methods: In a prospective controlled study, we enrolled 91 patients with chronic otitis media, all of who underwent canal wall up mastoidectomy with tympanoplasty via retroauricular approach. They were randomly assigned to the PAM-sutured (n = 45) or PAM-non-sutured (n = 46) group. Helical-mastoid distance and concho-mastoid angle were measured serially. Results: In both groups, helical-mastoid distance was significantly longer than preoperatively until 1 month postoperatively but was similar to preoperatively by 6 months. Concho-mastoid angle increased significantly until 1 month after surgery in the PAM-non-sutured group but returned to the preoperative value at 6 months postoperatively. In the PAM-sutured group, concho-mastoid angle increased significantly at 3 days postoperatively, was similar to preoperatively at 1 month after surgery, and became narrower than preoperatively at 6 months postoperatively. In both groups, there were significant effects of time on the changes in helical-mastoid distance or concho-mastoid angle. Group assignment did not significantly affect these time-related changes. Conclusion: PAM suturing did not affect helical-mastoid distance by 6 months postoperatively, but it did reduce the concho-mastoid angle to below the preoperative value at 6 months. We recommend that PAM be left severed to maintain concho-mastoid angle in the long term when using the retroauricular approach.